اثبات الزواج الالكتروني - ونان سارة نويصر فاتن (جامعة المسيلة, 2024)
Electronic marriage is one of the contracts that have emerged from technological developments, and due to its sensitivity compared to other contracts, there has been a jurisprudential debate about its legitimacy and how to prove it, especially since it is done through electronic means in which there is often fraud and deception. Even those who allow it have emphasized the need for precaution in this regard. Our aim from studying it was to shed light on the means of proving it, but this initially required clarifying its nature. To achieve the objectives, we combined several approaches, namely the descriptive and comparative methods. We concluded that it is a contract that does not differ from the traditional marriage contract in terms of definition, pillars, and condition, but it differs in the means used to conduct it. The contract session in it not a real session, but it can be considered a virtual session if it is done through written electronic means, and a mixed session if it is done through audio and visual means. The means of proving it should be compatible with its nature, which should be electronic means. The Algerian legislator has not adopted this contract, and one of the recommendations we have made is that if the Algerian legislator wants to adopt it, it is necessary to prepare the environment for that by establishing specialized body to register this contract and its methods of proof, and to add legal texts that take into account the virtual and mixed session and determine the legally accepted means for conducting it and the electronic means for proving it.
Keywords: proof - Marriage - Electronic